Meningkatkan Pemahaman Karakter Dasar Siswa Sekolah Menengah Pertama melalui Layanan Informasi - Kusuma, Cempaka Wuryani (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this research is to obtain empirical data about the increased understanding of the basic character of students through the information service. This type of research is experimental research design that is one group pretest-posttest involving a sample of eighth grade students at SMP Negeri 34 Semarang with the number of 32 students selected by using purposive sampling technique. Data was collected using a test instrument understanding of basic character. Data were analyzed using descriptive percentage and t-test. The results showed that the average student understanding of basic characters that are in the high category, with an average percentage of 69.48%. After being given the information included in the category of service is very high with a percentage of 90.85% resulting in an increase of 21:37%. Further results of t-test showed that the change in understanding of the fundamental character of students before and after the information services was highly significant (t (31) = 30.312, p <.01). Conclusions from this research is understanding the basic character of eighth grade students of SMP Negeri 34 Semarang G academic year 2015/2016 can be enhanced through information services.